Relationship of Corporate Performance with Stock Returns Across Large-Cap, Mid-Cap, and Small-Cap Firms : Fresh Insights from India - Faniband, Muhammadriyaj; Jadhav, Pravin (Indian Journal of Finance, 2025)
Purpose : This study investigated how company-specific factors such as net sales, net profit, and earnings per share (EPS) correlate with stock returns across large, mid, and small-cap (LMS) companies. Design/Methodology/Approach : We employed panel cointegration and panel causality models for quarterly data between June 2010 and March 2022. Findings : We found no evidence of long-term cointegration between company-specific factors and stock returns among LMS firms. Additionally, fluctuations in net sales and net profit were found to affect stock returns for large-cap and mid-cap companies, whereas EPS did not influence stock returns for LMS firms. Overall, the results of our cointegration and causality tests were consistent across LMS stocks. Practical Implications : The findings have practical implications for various stakeholders. Investors can use insights from our research to make more informed decisions regarding stock investments across LMS stocks. Understanding the long-term relationship between firm performance metrics and stock returns could help in portfolio management and risk assessment. Originality/Value : Based on our current information, this paper is the first to cover the association between firm performance and the stock returns of the mid-cap and small-cap firms, along with large-cap firms, for better investment diversification.